The Induna's Wife - Mitford, Bertram, 1855-1914; McCormick, A. D. (Arthur David), 1860-1943 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Induna's Wife" by Bertram Mitford is a historical novel written in the late 19th century. The story revolves around the Zulu warrior Untuswa, who faces political intrigue, personal conflict, and supernatural challenges in a time marked by war and the quest for power. The narrative hints at themes of loyalty, love, and the influence of magic within a richly detailed historical setting. At the start of the novel, the reader is introduced to Untuswa as he grapples with the ominous atmosphere surrounding the old Kambula Camp, a site laden with memories of recent bloodshed. As the evening progresses, he encounters his friend, Untuswa, who begins to tell a story about the mysterious "Red Death" plaguing their people. This sets the stage for Untuswa's unfolding journey, which will intertwine personal stakes and broader historical narratives against the backdrop of Zulu culture and conflict. The prologue establishes a sense of foreboding and anticipation, revealing complexities in personal relationships that will impact Untuswa's fate as the story unfolds. (This is an automatically generated summary.)
Release date is 2010-06-20
Produced by Nick Hodson of London, England
Keywords: Historical fiction; Zulu (African people) -- Fiction; Ndebele (African people) -- Fiction; South Africa -- History -- 19th century -- Fiction